A case report of lower urinary tract symptoms - Teixeira, Inês Domingues (2017)
Introduction: Benign prostatic hyperplasia (BHP) is one of the most prevalent benign disorders in men. The diagnosis is essentially clinic and typically characterized by low urinary tract symptoms (LUTS), a frequent cause of clinical consultation with a significant impact on quality of life. However, as LUTS can have many etiologies, the journey to the final diagnosis can be a challenge for the family doctor. Case report: An 88 year-old male, with a previous history of BHP, knees osteoarthritis, arterial hypertension, atrial flutter, diabetes, parkinsonian tremor, heart failure and obesity. In June 2013, the patient reports a history of LUTS with years of evolution, with predominantly urine storage symptoms such as urgency, increased urinary frequency and a marked noctúria. He complains of progressive fatigue with years of evolution and dyspnea on moderate exertion. After introduction and optimization of therapy directed to BHP and heart failure, the patient kept avoiding the diuretic because it intensifies the urinary symptoms. In October 2014 after presenting failure of urinary symptom control despite therapy, the patient was referred to an urologist where the diagnosis of urethral stricture was made. Comment: The unusual urinary symptoms that the patient had, the inexistence of abnormal complementary tests results suggesting urethral stricture and the presence of several confounding factors (heart disease, diabetes and resistance in taking diuretic) contributed to the low suspicion of this diagnosis. However, the valorization of patient’s complaints and a systematic monitoring of patient’s symptoms over time were the key to the diagnosis and therapeutic choice in order to manage a better control of the patient’s complaints.